1998
DOI: 10.1021/es970722z
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Enhanced Remediation of a Trichloroethene-Contaminated Aquifer. 2. Transport of TCE

Abstract: Field studies were conducted under an induced gradient in a trichloroethene (TCE)-contaminated aquifer at Picatinny Arsenal, NJ, to study (a) the rate-limited desorption of TCE from aquifer sediments to water and (b) the effect of a surfactant (Triton X-100) on the desorption and transport of TCE. Clean water was injected into the contaminated aquifer for 206 day. Triton X-100 was added for a 36-day period (days 36-71 from the start of clean water injection). The effect of Triton X-100 on the desorption and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Although this condition can be met by applying very large quantities of surfactant to the system (i.e., X CMC) (13,14), it is desirable to explore conditions for effective soil/solid remediation by use of reduced surfactant loads. In studies of contaminant desorption from soil, it has been shown that low to moderate levels of some surfactants can significantly increase the rate of desorption by increasing the mass-transfer coefficients of contaminants (14,15,(20)(21)(22). In such studies, it is equally important to elucidate the effect of the added surfactant on the contaminant distribution coefficient between soil and water as it would also affect the rate of desorption by changing the contaminant concentration gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Although this condition can be met by applying very large quantities of surfactant to the system (i.e., X CMC) (13,14), it is desirable to explore conditions for effective soil/solid remediation by use of reduced surfactant loads. In studies of contaminant desorption from soil, it has been shown that low to moderate levels of some surfactants can significantly increase the rate of desorption by increasing the mass-transfer coefficients of contaminants (14,15,(20)(21)(22). In such studies, it is equally important to elucidate the effect of the added surfactant on the contaminant distribution coefficient between soil and water as it would also affect the rate of desorption by changing the contaminant concentration gradient.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of surfactants enhanced the recovery, possibly by reducing the tortuosity of the soil organic matter (Sahoo et al, 1998). Decrease in tortuosity might be due to two mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…During the sorptiondesorption process, there are mainly three reactions occurring such as: (1) the dissolution of PAHs in the micelle phase, (2) the sorption of surfactant in the soil phase, (3) the partition of PAHs between aqueous and soil phase [7]. As all of three reactions reach equilibrium, the partition coefficient is defined as the ratio between the concentration of the PAHs in the soil phase and in the liquid phase (water+micelle), respectively.…”
Section: Pahs Sorption-desorpiton Phenomenamentioning
confidence: 99%